The composer as intellectual : music and ideology in France 1914-1940 - Fulcher, Jane F. (Oxford University Press, 2005)
As a follow-up to her book exploring musical and political cultures in France from the Dreyfus Affair to the First World War, the author here applies the same approach to the years from 1914-1940, arguing that French musical meanings are best explained not in terms of artistic movements, but rather in terms of the political culture.